2019
DOI: 10.1088/1742-6596/1341/2/022008
|View full text |Cite
|
Sign up to set email alerts
|

Studies on microplastic contamination in seagrass beds at Spermonde Archipelago of Makassar Strait, Indonesia

Abstract: There is growing awareness and concern on microplastics pollution in marine environments. Seagrasses are among the most productive shallow water ecosystems, serving a diverse assemblage of fish and invertebrates. Sediment and benthic animal samples collected from small islands at Spermonde archipelago confirmed the presence of microplastics with different levels of contamination. The occurrence of microplastics for up to 28.29% and 25% of contamination level in sediments and benthic animals, respectively, clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…A study reported that Holothuria floridana , Thyonella gemmate , and Cucumaria frondose ingested 2–20 times more filter feeders have been reported to ingest MPs which decreases their filtration ability leading to effects like neurotoxicity and immunotoxicity (Mohsen et al 2019 ; Bulleri et al 2021 ). In 2019, marine biologists reported that seagrass beds in Makassar Strait, Indonesia, contain MP contaminants in the form of beads, pellets, fragments, and fibers (Tahir et al 2019 ). Zooplankton also ingests MP beads which upon excretion can stick to the exoskeleton and appendages (Hasegawa and Nakaoka 2021 ).…”
Section: Bioaccumulation and Ecotoxicological Repercussions Of Mpsmentioning
confidence: 99%
“…A study reported that Holothuria floridana , Thyonella gemmate , and Cucumaria frondose ingested 2–20 times more filter feeders have been reported to ingest MPs which decreases their filtration ability leading to effects like neurotoxicity and immunotoxicity (Mohsen et al 2019 ; Bulleri et al 2021 ). In 2019, marine biologists reported that seagrass beds in Makassar Strait, Indonesia, contain MP contaminants in the form of beads, pellets, fragments, and fibers (Tahir et al 2019 ). Zooplankton also ingests MP beads which upon excretion can stick to the exoskeleton and appendages (Hasegawa and Nakaoka 2021 ).…”
Section: Bioaccumulation and Ecotoxicological Repercussions Of Mpsmentioning
confidence: 99%
“…Dominasi warna biru dari mikroplastik juga ditemukan pada penelitian sebelumnya di ikan (Ory et al, 2017;Wicaksono et al, 2020). Selain itu, tingginya kelimpahan mikroplastik berwarna biru pada penelitian ini juga sesuai dengan penelitian sebelumnya di perairan Kepulauan Spermonde Makassar yaitu lamun (Datu et al, 2019), air laut (Afdal et al, 2019), dan sedimen (Tahir et al, 2019a). Setiap jenis ikan diketahui memiliki sensitivitas terhadap warna makanannya dan juga warna lingkungan (Zhang et al, 2015).…”
Section: Kelimpahan Mikroplastik Pada Spesies Ikan Berbedaunclassified
“…Translokasi mikroplastik dapat terjadi di dalam organ insang, saluran pencernaan, daging (Barboza et al, 2019). Akumulasi mikroplastik juga ditemukan pada organisme bentik di perairan Kepulauan Spermonde, Makassar (Tahir et al, 2019a) dan juga pada ikan konsumsi yang dikumpulkan di Pasar Ikan Paotere, Makassar (Rochman et al, 2015). Akumulasi mikroplastik di perairan laut tentunya memberikan ancaman terhadap kesehatan ikan-ikan ekonomis penting.…”
unclassified
“…The particles currently existing in the Java sea are assumed to have originated from the South China Sea and the Pacific Ocean (Handyman et al, 2019). Meanwhile, the microplastics found in the Spermonde Islands of Makassar Gulf were contaminating seagrass beds (Tahir et al, 2019) and Muara Jagir of Surabaya City (Firdaus et al, 2020). The fishes from Trichiurus sp.…”
Section: Introductionmentioning
confidence: 99%